2021
DOI: 10.3390/s21248372
|View full text |Cite
|
Sign up to set email alerts
|

Partial Discharge and Internet of Things: A Switchgear Cell Maintenance Application Using Microclimate Sensors

Abstract: This paper proposes a solution for the development of microclimate monitoring for Low Voltage/High Voltage switchgear using the PRTG Internet of Things (IoT) platform. This IoT-based real time monitoring system can enable predictive maintenance to reduce the risk of electrical station malfunctions due to unfavorable environmental conditions. The combination of humidity and dust can lead to unplanned electrical discharges along the isolators inside a low or medium voltage electric table. If no predictive measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Data collected for microclimate regulation are intended to be accessed by public and organic certification bodies and integrated with Internet-of-things-based real-time monitoring systems based on cloud platforms [92] or edge-distributed computer systems [93].…”
Section: Interconnections Between Parametersmentioning
confidence: 99%
“…Data collected for microclimate regulation are intended to be accessed by public and organic certification bodies and integrated with Internet-of-things-based real-time monitoring systems based on cloud platforms [92] or edge-distributed computer systems [93].…”
Section: Interconnections Between Parametersmentioning
confidence: 99%
“…When 0 q  , the two roots of Equation ( 18) are real roots and different signs. The singularity at this time is unstable, and the steady state motion of the energy cannot be achieved [22]. When 0 q  and 0 p  , the singularity is stable, and the steady state motion of the energy collector can be achieved.…”
Section: Characteristics Of Energy Collector (Ec)mentioning
confidence: 98%
“…If a full condition monitoring system for switchgear is utilized, such as in [ 45 ], it would yield a reduction of 65% in three-year maintenance tasks, increasing the maintenance cycle by 30% and undoubtedly having a positive impact on cost reduction, and ultimately, ensuring a reliable long term switchgear operation. The safety study of ship power failures [ 46 ], concluded that in many power failures caused by worn or old components, the root sources were actually deficiencies in the maintenance system.…”
Section: Applications Of Measurement Data Manipulationmentioning
confidence: 99%
“…The implementation of real switchgear operation data will positively impact the overall accuracy of the digital twin, especially in the context of digital twins for ships. Additionally, using effective condition monitoring may reduce maintenance tasks by 65%, saving costs in labor and parts, while also reducing the risk of equipment damage during unnecessary inspections, decreasing failure probability, and optimizing the complete maintenance program [ 45 ].…”
Section: Applications Of Measurement Data Manipulationmentioning
confidence: 99%